Regulating Quality : Let Competing Firms Offer a Mix of Price and Quality Options - Baker, Bill; Tremolet, Sophie (World Bank, Washington, DC, 2012)
In many developing countries, the regulation of infrastructure service standards is rigid, and makes services too expensive for the poor. The current wave of liberalization of infrastructure, is an opportunity to address this problem. Debate on expanding access under such reform, has so far centered on price, not quality. This note proposes a new regulatory framework, where large, and small providers compete to supply a range of services at prices that better reflect consumer willingness to pay.